The perfect storm. An analysis of the processes that increase lethal violence in Mexico after 2006 - Flores Martínez, Iván (Trends in organized crime, 2022)
Research on ‘the War on Drugs’ in Mexico finds that military interventions increase lethal violence in the country. However, these studies fail to account for other processes that may be driving the behavior of lethal violence in the Mexican municipalities. We find confirmation that these rival processes influence the relative impact that military interventions have on lethal violence. In particular, we find that seasonality in violence, competition for scarce resources and PAN’s governance in the municipalities are associated with higher levels of lethal violence, as measured by the young male homicide rate. We argue that the literature may have overestimated the effect that military interventions have in lethal violence in municipalities and that other drivers of violence should be taken into account to accurately measure the impact that military interventions have on lethal violence.